COMPARISON OF URBAN FORM PARAMETERS OF LAHORE WITH ITS NEIGHBORING CITIES (Pakistan Journal of Science, 2016)
Urban form is the spatial imprint of urban transportation and associated land-use. It may be computed by various measures i.e. population density, employment density, Mix Density Index, Entropy Index, accessibility index, etc. No study has been conducted to explore the urban form of cities in Punjab. The objective of this studywas to compute and explain the urban form and compare its urban form variables in Lahore with neighboring Towns i.e. Ferozewala, Kasur, Pattoki, Sharaqpur and Muridkey. Lahore being the largest populated city of Punjab havinga monocentric and dense urban structure has changed during the last several years, preliminary analysis showed that Lahore has sprawl type of urban form whereas Muridkey, Kasur, Sharaqpur, Pattoki and Ferozewala have different types of urban forms varying from polycentric to monocentric. The urban form variables have the larger values for Lahore as compared to other neighboring cities. For making policy decisions related to different sectors like Transportation, Health and Education etc.it is recommended to conduct a thorough longitudinal study of urban form and to formulate the policies accordingly.
Keywords: Urban form Lahore; Population Density; Entropy Index; Accessibility Index; Mix Density Index